Twin pregnancy following sirolimus therapy in lymphangioleiomyomatosis - Andrea YLB,; Mas Fazlin MJ,; Ng, BH; Nik Nuratiqah NA,; Mohamed Faisal Abdul Hamid, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Lymphangioleiomyomatosis (LAM) is an orphan cystic lung disease which can occur sporadically or in association with tuberous sclerosis complex (TSC). We report a 26-year-old woman diagnosed with forme fruste of LAM, who presented with bilateral pneumothoraces requiring both surgical and medical pleurodesis. Clinical examination and investigations revealed hepatic and renal angiomyolipomas, a left retinal hamartoma, subcortical tubers and subependymal nodules in the brain as well as diffuse bilateral thin-walled lung cysts of varying sizes bilaterally. The histopathological examination (HPE) of the lung biopsy confirmed LAM. She was treated with 12 months of sirolimus with sustained effects on lung function and cystic lung lesions. Eight months post cessation of sirolimus, she conceived and delivered twins at 30 weeks. We describe the efficacy and safety of sirolimus and the successful twin pregnancy in a patient with LAM. This case highlights that treatment with sirolimus and surgical and medical pleurodesis was successful in preventing any further worsening of lung function.